Bancários e terceirizados no teleatendimento: funções iguais, realidades distintas - Barreto Júnior, José Orígenes Rabelo (2012)
This study aims to discuss the employment relationship between banks and outsourced telemarketing operators. The research also aims to identify the profile, working conditions and gender issues these professionals who present the twentyfirst century as workers in reshaped called information society. Search also check what are the marks of distinction teleoperators, which despite carrying the same functions, in most cases the same physical space, have structural differences that open a gap in the daily reality experienced by workers. In this sense it is initially presented the origins and characteristics of call centers. After that it is discussed the profile and gender issues in the sector. The third stage consists in the discussion about working conditions. The fourth chapter discusses the political dispute between the union and the employee representation bodies. It is also observed that this is a category that resists the pressure of a grueling work routine, repetitive and controlled, subject to a continuous flow of links. They are professionals who live daily with bullying, discrimination, lack of identity and devaluation